واقع التربية العملية في تعليم اللغة العربية لغير الناطقين بها من قبل الطلبة المعلمين في المدارس بأشيه - Abdullah, Abdullah; Ridha, Muhammad (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2024)
The aim of this study is to explore the reality of field experience in teaching Arabic to non-native speakers by answering the following main question: What is the reality of field experience in the Arabic language teaching program in schools in Aceh? The researcher used a questionnaire consisting of 62 items, divided into four areas: cooperation with practicum schools, effectiveness of university supervisors, evaluation of practicum students, and the relevance of theoretical content to the needs of schools. The study involved 82 practicum students from four Islamic universities in Aceh. The researcher used the SPSS statistical analysis program to calculate means, standard deviations, and conducted independent ttests and ANOVA tests to examine the impact of variables such as gender, cumulative GPA, and university on the reality of field experience. The results showed statistically significant differences in several areas, such as the effectiveness of university supervisors and cooperation between schools and universities. The researcher recommends increasing the number of credit hours for field experience, offering courses on theoretical content with practical activities such as micro-teaching, as well as developing evaluation mechanisms and improving coordination with practicum schools to enhance the quality of training.